Role of STIM1 (Stromal Interaction Molecule 1) in Hypertrophy-Related Contractile Dysfunction. Issue 2 (7th July 2017) - Troupes, Constantine D.; Wallner, Markus; Borghetti, Giulia; Zhang, Chen; Mohsin, Sadia; von Lewinski, Dirk; Berretta, Remus M.; Kubo, Hajime; Chen, Xiongwen; Soboloff, Jonathan; Houser, Steven
Abstract : Rationale: : Pathological increases in cardiac afterload result in myocyte hypertrophy with changes in myocyte electrical and mechanical phenotype. Remodeling of contractile and signaling Ca 2+ occurs in pathological hypertrophy and is central to myocyte remodeling. STIM1 (stromal interaction molecule 1) regulates Ca 2+ signaling in many cell types by sensing low endoplasmic reticular Ca 2+ levels and then coupling to plasma membrane Orai channels to induce a Ca 2+ influx pathway. Previous reports suggest that STIM1 may play a role in cardiac hypertrophy, but its role in electrical and mechanical phenotypic alterations is not well understood. Objective: : To define the contributions of STIM1-mediated Ca 2+ influx on electrical and mechanical properties of normal and diseased myocytes, and to determine whether Orai channels are obligatory partners for STIM1 in these processes using a clinically relevant large animal model of hypertrophy. Methods and Results: : Cardiac hypertrophy was induced by slow progressive pressure overload in adult cats. Hypertrophied myocytes had increased STIM1 expression and activity, which correlated with altered Ca 2 + -handling and action potential (AP) prolongation. Exposure of hypertrophied myocytes to the Orai channel blocker BTP2 caused a reduction of AP duration and reduced diastolic Ca 2+ spark rate. BTP2 had no effect on normal myocytes. Forced expression of STIM1 in cultured adult feline ventricular myocytes increased diastolic spark rate and prolonged AP duration. STIM1 expression produced an increase in the amount of Ca 2+ stored within the sarcoplasmic reticulum and activated Ca 2+ /calmodulin-dependent protein kinase II. STIM1 expression also increased spark rates and induced spontaneous APs. STIM1 effects were eliminated by either BTP2 or by coexpression of a dominant negative Orai construct. Conclusions: : STIM1 can associate with Orai in cardiac myocytes to produce a Ca 2+ influx pathway that can prolong the AP duration and load the sarcoplasmic reticulum and likely contributes to the altered electromechanical properties of the hypertrophied heart. Abstract : Supplemental Digital Content is available in the text.